2021
DOI: 10.1002/ece3.7736
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of bumble bee vitellogenin and vitellogenin‐like genes

Abstract: Vitellogenin (Vg), a storage protein, has been significantly studied for its egg yolk precursor role in oviparous animals. Recent studies found that vitellogenin and its Vg‐like homologs were fundamentally involved in many other biological processes in social insects such as female caste differences and oxidative stress resilience. In this study, we conducted the first large‐scale molecular evolutionary analyses of vitellogenin coding genes ( Vg ) and Vg‐like genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
0
6
1
Order By: Relevance
“…The dN / dS ratios indicated that the branch leading to the common ancestor of termite Vg4 was relatively under weak purifying selection but not in termite Vg1−2 clades (Supporting Information: Figure S2, Table S4). This is not contradicted by the evidence in the bumble bee genus Bombus , which indicated that Vg‐like genes showed a general tendency of relaxation of purifying selection (Zhao et al, 2021). Considering the inferred phylogenetic relationships of insect Vg genes, it is possible that termite Vg4 has diverged less from the outgroups compared to the other termite Vg1−3 genes.…”
Section: Discussionmentioning
confidence: 90%
“…The dN / dS ratios indicated that the branch leading to the common ancestor of termite Vg4 was relatively under weak purifying selection but not in termite Vg1−2 clades (Supporting Information: Figure S2, Table S4). This is not contradicted by the evidence in the bumble bee genus Bombus , which indicated that Vg‐like genes showed a general tendency of relaxation of purifying selection (Zhao et al, 2021). Considering the inferred phylogenetic relationships of insect Vg genes, it is possible that termite Vg4 has diverged less from the outgroups compared to the other termite Vg1−3 genes.…”
Section: Discussionmentioning
confidence: 90%
“…Selection pressures associated with social phenotypic plasticity impact the molecular evolution of proteins 83 . We thus explored the rate of protein evolution (dN/dS) for each single-copy orthogroup in the six Vespa and Vespula species (branch models: Supplementary Tables ST8–ST16; branch-site models: Supplementary Tables ST17-ST24).…”
Section: Resultsmentioning
confidence: 99%
“…We focused on vitellogenins and immune effectors in our proteomics analysis to examine whether their expression patterns supported the existence of a trade-off. Vitellogenin is an egg yolk protein precursor, but there are four distinct vitellogenin and vitellogenin-like genes in bumble bees [ 42 ] and the proteins are likely multifunctional, as has been shown in other social insects [ 43 ]. Differences in the proteins' domains indicate that they likely have distinct functions, but they have not yet been clearly defined.…”
Section: Discussionmentioning
confidence: 99%